Malaria-related anaemia: a Latin American perspective (2011)
ABSTRACT: Malaria is the most important parasitic disease worldwide, responsible for an estimated 225 million clinical cases each year. It mainly affects children, pregnant women and non-immune adults who frequently die victims of cerebral manifestations and anaemia. Although the contribution of the American continent to the global malaria burden is only around 1.2 million clinical cases annually, there are 170 million inhabitants living at risk of malaria transmission in this region. On the African continent, where Plasmodium falciparum is the most prevalent human malaria parasite, anaemia is responsible for about half of the malaria-related deaths. Conversely, in Latin America (LA), malaria-related anaemia appears to be uncommon, though there is a limited knowledge about its real prevalence. This may be partially explained by several factors, including that the overall malaria burden in LA is significantly lower than that of Africa, that Plasmodium vivax, the predominant Plasmodium species in the region, appears to display a different clinical spectrus and most likely because better health services in LA prevent the development of severe malaria cases. With the aim of contributing to the understanding of the real importance of malaria-related anaemia in LA, we discuss here a revision of the available literature on the subject and the usefulness of experimental animal models, including New World monkeys, particularly for the study of the mechanisms involved in the pathogenesis of malaria.